A STUDY OF LONG BEAN VEGETABLE MARKETING (Vigna Sinesis L) IN AMBULU DISTRICT, JEMBER REGENCY - Syamsul Hadi; Evita Soliha Hani (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Long bean vegetable farming in Ambulu Subdistrict, Jember Regency has a huge potential as indicated by the high demand for these vegetables. However, the price of long beans in Jember Regency at the retail level is too high and has implications for high marketing margins. The objectives of this study are: 1) To determine the performance pattern of long bean marketing channels formed, 2) Analyze the marketing value of long beans, and 3) Analyze the elasticity of long price transmission. The research method used is descriptive method with survey techniques and snowbolling sampling. To achieve the research objectives, each approach uses descriptive analysis, farmer's share (marketing efficiency), and price transmission elasticity. The results of the study revealed that 1) The pattern of long bean marketing channels formed by two channel patterns, namely the second and first level channels, 2) The first (second level) marketing channel pattern has a marketing margin of IDR 3,383 per kg, and the second marketing channel pattern (level one) has a marketing margin of IDR 1,500 per kg, and 3) The pattern of established marketing channels generally has a price transmission elasticity of Et = 1.17 and the shape of the lead market structure Oligopoly.